2013
DOI: 10.1177/0022034513517713
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Oral Bacterial Levels Predict Early Childhood Caries Development

Abstract: Objective: To calculate the association of maternal salivary bacterial challenge (mutans streptococci [MS] and lactobacilli [LB]) from pregnancy through 24 months' postpartum with child caries incidence (≥1 cavitated or restored teeth) at 36 months. Materials & Methods: Dental, salivary bacterial, sociodemographic, and behavioral measures were collected at three-to six-month intervals from a birth cohort of low-income Hispanic mother-child dyads (N = 243). We calculated the relative child caries incidence, ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
0
7

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(61 citation statements)
references
References 32 publications
(37 reference statements)
0
52
0
7
Order By: Relevance
“…Optimal oral health of women is especially important because of the material-child transmission of oral bacteria and the potential associated risk for dental caries [14,15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Optimal oral health of women is especially important because of the material-child transmission of oral bacteria and the potential associated risk for dental caries [14,15].…”
Section: Discussionmentioning
confidence: 99%
“…Most participants had not heard of fluoride and even those who had, did not understand its importance in caries prevention [14]. "El barniz, ¿no es el mismo que le llaman el esmalte?"…”
Section: Fluoride and Its Role In Preventing Dental Caries-themementioning
confidence: 99%
“…Similarly, parental dental status at age 10 was related to adult oral health among three different birth cohorts (born 1929-1938, 1939-1948 and 1959-1960) in Norway (Holst and Schuller 2012). To further corroborate intergenerational effects, a small study from the US among a low-income Hispanic cohort found that mothers' levels of cariogenic bacteria in their saliva were related to levels of caries experienced by their children (Chaffee et al 2014). The authors suggest that the association is likely to be due to shared environmental factors, as well as direct maternal-to-child transfer of bacteria.…”
Section: Childhood Socio-economic Background and Adult Levels Of Diseasementioning
confidence: 99%
“…Although infants may not have tooth eruptions at the time of these exposures, the pathogens can still colonize the infant's oral cavity and begin to impact the developing teeth so that they are more susceptible to caries and periodontal disease [22].…”
Section: Maternal Oral Health Factorsmentioning
confidence: 99%